Constructive Alignment of Islamic Education Curriculum in Doctoral Program at Sunan Kalijaga Yogyakarta - Aida Hayani; Sutrisno Sutrisno; Sukiman Sukiman (STAI Hubbulwathan Duri, 2022)
One of the problems faced by the Islamic Religious Education Doctoral Program (PAI) at UIN Sunan Kalijaga is curriculum issues. Where the curriculum must be designed to be research-oriented with an inter, multi and transdisciplinary approach to find solutions to various PAI problems, so as to gain recognition both nationally and internationally. The purpose of this research is to increase knowledge and understanding regarding the Curriculum Design of the PAI Doctoral Program to anticipate various PAI problems. The method used is a field study, this study aims to reveal the curriculum design of the PAI doctoral study program at UIN Sunan Kalijaga. Data collection was carried out by in-depth interviews with Head of Study Program, Head of LPM, Dean and Students. Results The researchers found that the curriculum design in the PAI Doctoral Program was in accordance with the procedures and mechanisms of curriculum design referring to the KKNI. That is, starting from the formulation of learning outcomes, the substance of the study materials to courses, learning designs and assessment designs but the construction aligment of the profile of Doctrol Programe, the description of level 9 in the KKNI, Study Materials and the determination of courses is still not appropriate, That will be affect to the quality of Doctoral Student’s in UIN Sunan Kalijaga